New beam delivery system design for industrial electron accelerator at Nuclear Science and Technology Research Institute, Iran. (June 2022) - Salehi, M.; Ghasemi, F.; Davani, F. Abbasi; Ansari, M.; Poursaleh, A.
Abstract: The output beams generated by industrial electron accelerators should be swept over the product. It is necessary to determine the exact scan length in order to ensure that an efficient dose reaches the product and to avoid the loss of the beam in contact with the sides of the product. Another challenge associated with scanning beams is the non-uniformity of the dose across the entire product during irradiation. In this study, the use of beam correction magnets is proposed for correcting products that receive a non-uniform dose. These magnets correct beams that are not swept in parallel. In addition, we simulated the dose received by the products in two non-uniform and uniform modes (modified by beam correction magnets) using the Monte Carlo method, and compared the results to assess the importance of using an appropriate irradiation system. Among the proposed magnets, a modified sector magnet is recommended for correcting the beam path and reducing the side effect. Using this magnet for a long horn does not require a cooling system, but using it for a short horn increases the need for a water-cooling system. Highlights: Investigation of dose distributions under parallel and diagonal irradiation modes using Monte Carlo method. Importance of accurate beam scanning angle for reducing power loss in industrial irradiation. Design of a new beam delivery system using beam correction magnets. Suitable magnets designed to enhance the irradiation of products.